Save the lives of Preterm through Kangaroo Mother Care in Pakistan - Muhammad Nasir (Liaquat National Journal of Primary Care, 2024)
Neonatal mortality remains a pressing global concern, with millions of infants succumbing to preventable causes within their first month of life. One promising solution that has gained attraction is Kangaroo Mother Care (KMC), an innovative and cost-effective approach that has demonstrated remarkable success in improving survival rates among newborns. Neonatal morbidity and mortality can be reduced by providing KMC to babies. KMC is a simple yet powerful intervention that involves continuous skin-to-skin contact between a mother and her preterm or low birth-weight infant. Pakistan bears a heavy burden of neonatal mortality, with a reported rate of 42 deaths per 1,000 live births as of the latest data. Implementing Kangaroo Mother Care in a country as diverse and populous as Pakistan presents a unique set of challenges. However, the government, non-governmental organizations (NGOs), and healthcare professionals have made commendable efforts to integrate KMC into the existing healthcare system.